Effect of Anticoagulating and Non-Anticoagulating Concentrations of Heparin on the Generalized Shwartzman Reaction - Corrigan, J. J (Thrombosis and Haemostasis, 1970)
Rabbits given 2 properly spaced intravenous injections of bacterial endotoxin develop bilateral renal cortical necrosis (generalized Shwartzman reaction - gSr). This renal lesion is the result of fibrin deposition secondary to diffuse intravascular clotting (DIC). Using this experimental model, the effect of anticoagulating (large) and non- anticoagulating (small) concentrations of heparin on the changes in blood platelets, plasma coagulation factors II, V, VIII and fibrinogen during the production of renal cortical necrosis was studied. The data demonstrate that all amounts of heparin given during, but not after, the period of intravascular clotting reduced the frequency of renal cortical necrosis. Anticoagulating concentrations completely prevented the renal lesion. Non-anticoagulating amounts could reduce the frequency of the renal lesions, but this effect was not predictable or consistent. Coagulation studies in the large dose group revealed thrombocytopenia reduced factors II, V, and VIII but no fibrinogen consumption. These findings suggest that heparin inhibits the formation of fibrin in vivo, thereby preventing the formation of renal cortical necrosis. The coagulation data in the small dose group differed in that fibrinogen consumption did occur. The possible explanations for the phenomenon were discussed.